FROM PESANTREN TO ONLINE NEWSPAPER: CONSERVATIVE AND PROGRESSIVE EXEGESIS IN KH. MUSTA’IN SYAFI’I’S TAFSIR AL-QUR’AN AKTUAL - Saadatul Jannah; Abd Moqsith; M. Dimas Mulana; M. Itsbatul Haq (Universitas Nurul Jadid, 2025)
Indonesian Qur’anic exegesis has undergone significant transformation alongside shifts in media, socio-political contexts, and interpretive orientations. While classical tafsir traditions were largely produced within pesantren and transmitted through printed texts, contemporary interpretations increasingly emerge in digital and mass-media spaces. This article examines Tafsir Al-Qur’an Aktual by KH. Musta’in Syafi’i, a Qur’anic commentary published in the online newspaper Harian Bangsa, focusing on how conservative and progressive exegetical tendencies are negotiated within this medium. The study aims to analyze the ideological orientations embedded in Musta’in Syafi’i’s interpretations and to explore how digital media reshapes pesantren-based Qur’anic discourse in contemporary Indonesia. Employing qualitative library research combined with Critical Discourse Analysis, the study analyzes selected tafsir texts addressing leadership, gender, public ethics, and religious authority. The findings demonstrate that Musta’in Syafi’i articulates a hybrid exegetical model that integrates classical pesantren epistemology with contextual and ethical engagement in modern socio-political debates. His tafsir exhibits progressive interpretations in areas such as social ethics, anti-corruption discourse, and gender participation in worship, while simultaneously maintaining conservative positions on religious authority, political identity, and ritual norms. This coexistence reflects the influence of the author’s ideological, educational, and socio-political pre-understandings. The study concludes that Tafsir Al-Qur’an Aktual represents a distinctive form of Indonesian Qur’anic interpretation that bridges traditional authority and contemporary public discourse, highlighting how digital media functions as a transformative space for negotiating continuity and change in Qur’anic exegesis.